Slow dance : a novel - Rowell, Rainbow (Reese's book club., 2024)
They were just friends. Best friends. Allies. They spent entire summers sitting on Shiloh's porch steps, dreaming about the future. They were both going to get out of north Omaha--Shiloh would go to go to college and become an actress, and Cary would join the Navy. They promised each other that their friendship would never change. Well, Shiloh did go to college, and Cary did join the Navy. And yet, somehow, everything changed. Now Shiloh's thirty-three, and it's been fourteen years since she talked to Cary. She's been married and divorced. She has two kids. And she's back living in the same house she grew up in. Her life is nothing like she planned. When she's invited to an old friend's wedding, all Shiloh can think about is whether Cary will be there--and whether she hopes he will be. Would Cary even want to talk to her? After everything? The answer is yes. And yes. And yes. Slow Dance is the story of two kids who fell in love before they knew enough about love to recognize it. Two friends who lost everything. Two adults who just feel lost. It's the story of Shiloh and Cary, who everyone thought would end up together, trying to find their way back to the start. --